SME internationalization in emerging markets: Symbiotic vs. commensal pathways - Andrey Mikhailitchenko; Sanjay B. Varshney (Journal of Marketing and Consumer Behaviour in Emerging Markets (JMCBEM), 2016)
Purpose - The purpose of this research is to develop, test, and validate the symbiotic networking concept of SMEs internationalization pathways. Design/Methodology/Approach - Survey data were collected from managers/owners of SMEs operating in the textile industry in China and Russia. The applied data analysis technique employed is structural equation modeling. The survey was pretested to address reliability, validity, and cross-cultural stability issues. Findings - The symbiotic networking relationships in SMEs were shown to be positively related to their degree of internationalization. The relationship between networking and internationalization is significantly stronger in the conditions of high rather than low environmental turbulence. Research Limitations/Implications - Further research should validate the findings in other industries and other countries. Future research may also include in the model other cultural, attitudinal, environmental, and managerial variables, as well as other dependent variables, first of all from consumer behavior and marketing communications fields. Practical Implications - The findings may assist in identifying networking clusters of SMEs in emerging economies that are more likely to enter foreign markets and develop more targeted support and educational programs aimed at facilitating the internationalization of small businesses. The research results also assist in the elaboration of managerial tools in multinational entrepreneurial businesses. Originality/Value - The research contributes to the field by empirically investigating, testing, and putting into a unified framework the measurement tools required for identifying the symbiotic networking interactions of SMEs and the influence of these interactions on SME internationalization pathways.
Keywords: C300; F230; M16; P200; O430; 650; international business; structural equation model; entrepreneurship; China; Russia